Quizizz as Technology to Enhance EFL Students' Active Participation in the Classroom - Rizqi Febrian Pramudita (Politeknik Negeri Jember, 2023)
It is essential that English be taught in schools and universities as a foreign language. However, many English learners do not devote themselves totally to acquiring the language. Additionally, teaching and learning (T&L) activities might occasionally become boring. Due to this matter, EFL students struggle to demonstrate active participation in class. This article intends to highlight how teachers can use Quizizz, a learning application, to enhance their students’ active involvement in studying English.